Comparative Study of Student Learning Outcomes between Online and Offline Learning at SMAN 22 Bone - Muh. Darwis; Fabiayyi Nurkuraeni; Nasaruddin Hasyim (Journal of Educational Development and Learning (JEDAL), 2024)
The Coronavirus Diseases 19 outbreak has had a major impact on the ongoing teaching and learning process, especially on student learning outcomes. This research aims to determine the comparison of student learning outcomes between online and offline learning. This research uses a quantitative approach with a quantitative descriptive research type. The sample in this study consisted of 76 students including 38 students in classes X and XI using simple random sampling techniques. The data obtained was analyzed using descriptive statistical analysis and inferential statistical analysis. The research results show that online learning and offline learning are in the quite high category. The average value of learning outcomes obtained by students during online learning is 81.96, lower than the average value of learning outcomes obtained by students during offline learning of 84. Based on the paired sample t-test or t test that has been carried out , it was concluded that there were significant differences in student learning outcomes between online and offline learning at SMAN 22 Bone. In contrast to previous studies which mostly used 2-3 variables, this research only uses a single variable which makes it easier for researchers to formulate the object or core of the research. This research is expected to provide a significant contribution to the understanding and development of better learning methods that are more appropriate to the needs of students at SMAN 22 Bone.